Volume dan Kapasitas Jaringan Jalan di Kawasan Pondok Labu - Said Djamaluddin; Adella Hotnyda Siregar; Pungkas Hendratmoko (Institut Transportasi dan Logistik Trisakti, 2015)
The intent of this study to analyze the optimization of highway network of hospitals Fatmawati to Pondok Labu (UPN “Veteran“ Jakarta). Especially for measuring the ratio of the volume and capacity (V/C) of the facilities and infrastructure, given the congestion level above the tolerance within 2-3 km of the RS Fatmawati-UPN